Two zebras and a cardiac arrest: a case report of concomitant Brugada syndrome and an anomalous coronary artery. Issue 6 (2nd December 2020) - Bates, Alexander; Ullah, Waqas; Wilkinson, James; Shambrook, James
Abstract: Background: Discovering concomitant diagnoses results in a challenge to determine the true cause of a patient's presentation. Evaluating this fully is vital to plan appropriate and avoid inappropriate therapy. Case summary: A 55-year-old gentleman presents in cardiac arrest whilst watching an unusual occurrence of England dominating a Football World Cup game vs. Panama in 2018. Diagnostic coronary angiography discovered an anomalous right coronary artery from the opposite sinus (R-ACAOS), but clinical suspicion this was incidental lead to a further diagnosis of Type 1 Brugada Syndrome (BrS) following a positive Ajmaline provocation challenge. Risk stratification of these two zebras using computed tomography coronary angiography (CTCA), Cardiac magnetic resonance imaging (CMRI), Exercise Stress Echocardiography was performed and following a multi-disciplinary meeting, BrS was felt to be the primary diagnosis. The patient received a secondary prevention implantation of a cardiac defibrillator and avoided cardiac surgery. Discussion: Diagnosing a rare condition does not necessarily mean it is the cause of a patient's presentation and should not end the investigative process. Right coronary artery from the opposite sinus rarely causes cardiac arrest in middle age and is typically associated with peak exercise. Type 1 BrS is associated with cardiac arrest with vagal activity, perhaps such as England winning a World Cup game! Clinical correlation and risk stratification is required for suspected incidental findings.